Green Cloud Technologies for SAP-driven Enterprises - Jampani, Sridhar; Gudavalli, Sunil; Ravi, Vamsee Krishna; Goel, Om; Jain, Arpit; Kumar, Lalit (Integrated Journal for Research in Arts and Humanities, 2024)
Green Cloud Technologies are rapidly transforming the landscape of enterprise IT solutions, particularly for SAP-driven businesses. As organizations increasingly turn to cloud computing for its scalability, flexibility, and cost-efficiency, the environmental impact of traditional data centers has raised significant concerns. Green Cloud Technologies aim to address these concerns by leveraging sustainable practices, renewable energy sources, and energy-efficient infrastructures in cloud data centers. For SAP-driven enterprises, which rely on complex, resource-intensive business processes, adopting green cloud solutions offers a dual benefit: reducing operational costs while supporting corporate sustainability goals. This paper explores the role of Green Cloud Technologies in SAP environments, highlighting the integration of energy-efficient systems, eco-friendly hardware, and sustainable cloud services. It also examines best practices for SAP-driven enterprises to optimize resource usage, minimize carbon footprints, and align with global environmental standards. By adopting Green Cloud solutions, businesses not only contribute to environmental conservation but also enhance their competitiveness by aligning with increasingly stringent regulatory requirements and stakeholder expectations for sustainability.